The Introvert Character as Seen In Tennessee William’s Glass Menagerie - Dian Paramita Sari; Feby Meuthia Yusuf; Helmita Helmita (Fakultas Sastra Universitas Ekasakti, 2017)
This thesis tell about a drama Glass Menagerie by Tennessee William. This drama memory play of narrator, Tom wingfield. He is an aspiring poet which work in warehouse to support his mother, Amanda and his sister, Laura. Mr. wingfield, Tom’s father, ran off family years ago, except for one postcard, has not been haeard from since. Amanda, originally from a genteel family, regales her children frequently with tales of her idyllic youth and the scores of suitors who once pursued her. She is disappointed that Laura, who wears a brace one her leg and is painfully shy, does not attract any gentlemen callers. Amanda then decides that Laura’s last hope must lie in marriage and begins selling magazine subscriptions to earn the extra money she believes will help to attract suitors for Laura.